(Un)productive Use of Public Debt in Kosovo - Zharku, Lutfi (Ekonomika, 2018)
[full article and abstract in English] The aim of this paper is to analyze how public debt is used in Kosovo and to find out if there is a direct link between public debt and public investment that has positive impact on economic growth. Since acquiring independence, Kosovo engaged in public investment on a large scale, mainly in developing road infrastructure. With the cash balance depleted, a growing budget deficit and facing liquidity difficulties due to ongoing large public investments and increasing wage & salary bill and social transfers, the Government of Kosovo had to start borrowing both abroad and domestically. However, public debt had continued to increase even though public investment had experienced a sharp decrease. Since the budget financial statements do not show any deficit composition, we have recalculated a special-purpose deficit, the so-called “regular” budget deficit, considering only regular receipts and outlays. By disaggregating the total public debt based on lenders and by tying the loans to specific capital projects, we came to the conclusion that only a small part of the public debt is directly tied with public investment, while the bulk of it is used to finance the budget deficit that was caused by a high increase in wage & salary bill and social transfers. The analysis confirms that the public debt is being used for unproductive purposes and therefore does not contribute to economic growth. All this was supported by a lack of legal infrastructure or fiscal rules for several years. There is extensive literature on both public debt and public investments as well as their impact on economic growth. The literature review method was adopted for this study, and our research was refined by including the selected papers that contained empirical and theoretical studies on these issues. This is a case study for Kosovo, and the research has been carried out using secondary research data drawn from Kosovo budget annual financial reports and annual bulletins on public debt. The implications of this paper may be of high importance for policymakers as well as for academics, as this happens to be one of the pioneering articles in this field in terms of studies conducted about Kosovo. Herein is presented a unique approach to the issues of public debt and public investment.